PENGARUH KUALITAS SISTEM, INFORMASI DAN LAYANAN SIAKAD ONLINE TERHADAP KEPUASAN MAHASISWA (Studi Pada Mahasiswa AKPINDO Jakarta) - Priyanto; Setyo Widiarto; Roby Darmadi (Eduturisma, 2019)
Abstract The development of information systems cannot be separated from the rapid progress of information technology and the internet. At present, this has changed the paradigm in business processes and policy making. Higher education institutions are no exception starting to use internet-based information systems as an alternative in the process of its activities. However, only few research has discussed the effect of online academic systems on student satisfaction. This study aims to analyse the effect of system quality, information quality and online service quality siakad on student satisfaction. Data were obtained by survey method of 255 students of the Indonesian Tourism Academy (AKPINDO) Jakarta with multiple linear regression methods. The results of the study revealed that the quality of academic information systems had no effect on student satisfaction, while information quality and service quality significantly affected student satisfaction. Simultaneously the quality of the system, information and services affect the satisfaction of students.